Neutrosophic Z-Number and HyperSoft for Integrated Energy Supply System Performance Inference of Solar Energy and Cogenerations - Weibin Wang; Chaofei Nie; Kang Li; Jianfeng Man (Neutrosophic Sets and Systems)
The increasing global demand for sustainable energy solutions has led to the development of integrated energy supply systems that combine solar energy and cogeneration technologies. So, this study proposes a decision-making approach to evaluate The Energy Supply System Performance of Solar Energy and Cogenerations. Two methods are applied in this study, such as SIWEC to compute the criteria weights and EDAS method to rank the alternatives. These methods are used under the neutrosophic Z-number (NZN). We used the HyperSoft set to deal with various criteria and sub criteria. This study applied the NZN model with nine criteria and eight alternatives. Three experts can evaluate these criteria and alternatives. We applied the sensitivity analysis under nine different cases. The results showed that the ranks of the alternatives are stable in different cases.